2020
DOI: 10.1016/j.jbspin.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of spinal ankylosis on bone trabecular fragility assessed on CT scans in patients with ankylosing spondylitis. A retrospective study

Abstract: Background: Ankylosing spondylitis (AS) patients seems to be at risk of osteoporosis but bone screening is not often performed. The objective was to evaluate the effect of vertebral ankylosis on scanographic bone attenuation coefficient (SBAC) on lumbar vertebrae in AS patients. Patients and methods: This study included AS patients fulfilling New York criteria who underwent both thoraco-abdomino-pelvic computed tomography and X-rays during routine follow-up. The modified stoke ankylosing spondylitis spinal sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…With immobilization, the autofused segments likely experience stress shielding and resulting loss of cancellous BMD. Other studies have made similar suggestions, notably recent studies by Lee et al [ 45 ] and Fauny et al [ 46 ]. Both groups analyzed spinal BMD in patients with AS, examining 47 and 73 patients, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…With immobilization, the autofused segments likely experience stress shielding and resulting loss of cancellous BMD. Other studies have made similar suggestions, notably recent studies by Lee et al [ 45 ] and Fauny et al [ 46 ]. Both groups analyzed spinal BMD in patients with AS, examining 47 and 73 patients, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…Previous cross‐sectional studies that used QCT demonstrated that lower lumbar tBMD was associated with the presence of syndesmophytes (25,26), more extensive spinal changes (24), or bridging (10,23), but the proliferative changes in these studies were not restricted to the lumbar spine. Only Karberg et al (25) limited the examination of syndesmophytes to the lumbar spine, and only 2 studies adjusted for patient age (24,26).…”
Section: Discussionmentioning
confidence: 96%
“…Despite these commonalities, whether, and how, these processes are related is not well understood. It has been hypothesized that bridging syndesmophytes may promote bone loss by reducing vertebral mobility (10). However, 2 longitudinal studies have suggested the inverse, that low bone mineral density (BMD) predicts syndesmophyte formation (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent study investigated the effect of vertebral ankylosis on scanographic bone attenuation coefficient (SBAC), measured from L1 to L5, in AS patients ( 105 ). It was found that patients with at least one bony bridge had lower SBAC values, while there was a correlation between the presence of full ankylosis and the probability of presenting SBAC ≤145 HU (fracture threshold), suggesting an impact of ankylosed vertebrae on trabecular bone deterioration.…”
Section: Psoriatic Arthritis and Spondyloarthritismentioning
confidence: 99%